HYBRID IDENTITY STEREOTYPING IN NOVEL THE SUN IS ALSO A STAR BY NICOLE YOON - Fadhilla, Aliya (Universitas Gunadarma, 2018)
Novel is a prose fiction with inconsiderable length and a certain complexity that deals imaginatively with human experience. This source of this research is novel The Sun is Also a Star (2016) by Nicola Yoon. This research focused on stereotypes quality towards people with hybrid identity which occurred in the novel. The method used in this research is qualitative methods because novel is a narrative text form which contains action in it. Stuart Hall’s concept is employed to analyse the research data. The discussion’s findings are some of the racism actions occur in the novel in form of verbal action related to physical ability, physical appearance, bad words, sexual, and someone’s trait. Not only verbally, the racism action is also represented by someone’s nature.